Social Unionism and Membership Participation: What Role for Union Democracy? - Ross, Stephanie (Studies in Political Economy, 2008)
[The author] brings to the pages of this journal two closely intertwined debates regarding the meaning of social movement unionism and strategies for rebuilding labour movement power in Canada and the United States. It offers an important overview of this debate and raises critical points about the meaning and place of union democracy. The author provides a pertinent critique of the “organizing unionism” “model” that has emerged in the United States. It also serves as a useful foil for distinguishing greater member participation of the sort called for by the organizing model from greater member control.
https://www.researchgate.net/profile/Stephanie-Ross-6/publication/277186366_Social_Unionism_and_Membership_Participation_What_Role_for_Union_Democracy/links/55f6cb7008aec948c462f309/Social-Unionism-and-Membership-Participation-What-Role-for-Union-Democracy.pdf